LTP saturation and spatial learning disruption: effects of task variables and saturation levels - Barnes, CA (J Neurosci, 1994)
The prediction that “saturation” of LTP/LTE at hippocampal synapses should impair spatial learning was reinvestigated in the light of a more specific consideration of the theory of Hebbian associative networks, which predicts a nonlinear relationship between LTP “saturation” and memory impairment. This nonlinearity may explain the variable results of studies that have addressed the effects of LTP “saturation” on behavior. The extent of LTP “saturation” in fascia dentata produced by the standard chronic LTP stimulation protocol was assessed both electrophysiologically and through the use of an anatomical marker (activation of the immediate-early gene zif268). Both methods point to the conclusion that the standard protocols used to induce LTP do not “saturate” the process at any dorsoventral level, and leave the ventral half of the hippocampus virtually unaffected. LTP- inducing, bilateral perforant path stimulation led to a significant deficit in the reversal of a well-learned spatial response on the Barnes circular platform task as reported previously, yet in the same animals produced no deficit in learning the Morris water task (for which previous results have been conflicting). The behavioral deficit was not a consequence of any after-discharge in the hippocampal EEG. In contrast, administration of maximal electroconvulsive shock led to robust zif268 activation throughout the hippocampus, enhancement of synaptic responses, occlusion of LTP produced by discrete high- frequency stimulation, and spatial learning deficits in the water task. These data provide further support for the involvement of LTP-like synaptic enhancement in spatial learning.